2012
DOI: 10.1038/ismej.2011.206
|View full text |Cite
|
Sign up to set email alerts
|

Temperature responses of carbon monoxide and hydrogen uptake by vegetated and unvegetated volcanic cinders

Abstract: Ecosystem succession on a large deposit of volcanic cinders emplaced on Kilauea Volcano in 1959 has resulted in a mosaic of closed-canopy forested patches and contiguous unvegetated patches. Unvegetated and unshaded surface cinders (Bare) experience substantial diurnal temperature oscillations ranging from moderate (16 1C) to extreme (55 1C) conditions. The surface material of adjacent vegetated patches (Canopy) experiences much smaller fluctuations (14-25 1C) due to shading. To determine whether surface mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Studies on existing volcanic systems have focused on microbial distribution and function in relation to lava flows, their ages and plant or ecosystem development (for review see[ 2 ]). The microbial diversity of volcanic deposits is poorly characterized, but several studies have shown that lava weathering partially regulates rates of nitrogen fixation in young Mauna Loa ecosystems (Hawai`i) [ 9 ], and is accompanied by changes in carbon monoxide oxidizer diversity during succession on recent volcanic deposits at Kilauea Volcano, Hawai`i[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on existing volcanic systems have focused on microbial distribution and function in relation to lava flows, their ages and plant or ecosystem development (for review see[ 2 ]). The microbial diversity of volcanic deposits is poorly characterized, but several studies have shown that lava weathering partially regulates rates of nitrogen fixation in young Mauna Loa ecosystems (Hawai`i) [ 9 ], and is accompanied by changes in carbon monoxide oxidizer diversity during succession on recent volcanic deposits at Kilauea Volcano, Hawai`i[ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ecological importance of this bacteria family in the grasslands dominated by the Nardion alliance is unknown. The few known Ktedonobacteria have been shown to prevail in such places as oligotrophic 44 and thermophilic 45 environments, and have been associated with carbon monoxide oxidation 46 . The family has recently been discovered further in the rhizosphere of Andropogon gerardii (big bluestem) grasses 19 , and is worthwhile investigating further.…”
Section: Discussionmentioning
confidence: 99%
“…; King and Weber ; Nacke et al. ; King and King ); Mauna Loa, Hawaii (Crews et al. ); Miyake Island, Japan (Ohta et al.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial communities associated with volcanoes have been studied in the lava flow soils, rocks, and/or glass found at Kilauea volcano, Hawaii (King 2003;Dunfield and King 2004;Nanba et al 2004;Gomez-Alvarez et al 2007;King and Weber 2008;Nacke et al 2011;King and King 2012); Mauna Loa, Hawaii (Crews et al 2001); Miyake Island, Japan (Ohta et al 2003); Llaima volcano, Chile (Hernandez et al 2014); and Mt. Hekla, Iceland (Kelly et al 2010).…”
Section: Introductionmentioning
confidence: 99%